Pathogenicity of isolates of the rice blast pathogen (Pyricularia oryzae) from Indonesia - Kadeawi, Santoso; Nasution, Anggiani; Hairmansis, Aris; Telebanco-Yanoria, Mary Jeanie; Obara, Mitsuhiro; Hayashi, Nagao; Fukuta, Yoshimichi (Scientific Societies, 2021)
A total of 201 isolates of Pyricularia oryzae (the causal agent of rice blast) were collected from three rice ecosystems (upland, lowland, and swampy) in five regions of Indonesia (West Java, Lampung, South Sumatra, Kalimantan, and Bali). Their pathogenicities were characterized based on the patterns of reaction of 25 differential varieties (DVs) and the susceptible control Lijiangxintuanheigu (LTH), which was susceptible to all blast isolates. A high proportion of isolates (>80.0%) were virulent to DVs for resistance genes Pib, Pit, Pia, Pik-s, and Pi12(t), and a low proportion of isolates (<12.9%) were virulent to DVs for Pik-m, Pi1, Pik-h, Pik, Pik-p, and Pi7(t). Virulence to the other DVs for Pish, Pii, Pi3, Pi5(t), Pi9(t), Piz, Piz-5, Piz-t, Pita-2 (two lines), Pita (two lines), Pi19(t), and Pi20(t) showed intermediate frequencies from 20.0 to 80.0%. These isolates were classified into three cluster groups, Ia, Ib, and II, and the frequencies of cluster groups varied between the three ecosystems and the five regions. The frequencies of cluster groups varied between ecosystems and regions, and races varied according to the ecosystems. A total of 27 standard differential blast isolates (SDBIs) were selected from the 201 isolates collected. The set of 25 DVs and these 27 SDBIs will be used as a new differential system for analysis of the pathogenicity of blast isolates and analysis of resistance genes in rice cultivars, which will contribute to building a durable protection system against blast disease in Indonesia.